Dual-Sliding-Mode-Observer-Based IPMSM Sensorless Control Technique - Sang Xu; Anwen Shen; Mingzhen Zhang; Qipeng Tang; Xin Luo; Jinbang Xu (Complexity)
Back electromotive force (EMF)-based sliding mode observer (SMO) is increasingly employed for interior permanent magnet synchronous machine (IPMSM) sensorless drives due to its high robustness to external disturbance and low sensitivity to system parameter variations. However, its control performance is severely weakened by the inherent chattering and speed iteration operation. In order to effectively resolve these problems, a strategy to design a dual-SMO is proposed in this paper. With the proposed strategy, the combination of the stator-voltage transformation matrix (SVTM) and the low-pass filter is developed to obtain the rotor position information, which greatly alleviates the chattering without any deviations. Meanwhile, three independent equations are constructed and extracted by placing two SVTMs in different locations. By solving these three equations, the rotor position can be calculated directly with zero phase shift, which eliminates the speed iteration operation and improves the system’s dynamic performance. Furthermore, by analyzing the influences of machine parameters’ variations, the suitable virtual q-axis inductance can be selected to quickly achieve the optimal-efficiency sensorless control of the IPMSM. Finally, the experimental results on an IPMSM demonstrate that the rotor position with good steady-state and dynamic performance can be obtained accurately by using the proposed sensorless control strategy.